2019
DOI: 10.1007/s40120-019-00168-1
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers for Alzheimer’s Disease and Related Disorders

Abstract: The search for accessible and cost-effective biomarkers to complement current cerebrospinal fluid (CSF) and imaging biomarkers in the accurate detection of Alzheimer disease (AD) and other common neurodegenerative disorders remains a challenging task. The advances in ultra-sensitive detection methods has highlighted blood biomarkers (e.g. amyloidb and neurofilament light) as a valuable and realistic tool in a diagnostic or screening process. Saliva, however, is also a rich source of potential biomarkers for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 82 publications
(100 reference statements)
2
57
0
1
Order By: Relevance
“…Therefore, due to the capacity of molecules to pass from the blood to the saliva through passive diffusion, active transport or microfiltration, saliva is a promising AD-related biomarker pool that could be used for its early and accurate diagnosis [ 147 , 148 ]. The most important AD biomarkers found within the saliva are Aβ peptides, T-tau and P-tau, acetylcholine, lactoferrin, and trehalose, each related to different AD pathophysiological mechanism.…”
Section: Saliva Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, due to the capacity of molecules to pass from the blood to the saliva through passive diffusion, active transport or microfiltration, saliva is a promising AD-related biomarker pool that could be used for its early and accurate diagnosis [ 147 , 148 ]. The most important AD biomarkers found within the saliva are Aβ peptides, T-tau and P-tau, acetylcholine, lactoferrin, and trehalose, each related to different AD pathophysiological mechanism.…”
Section: Saliva Biomarkersmentioning
confidence: 99%
“…Owing to the saliva–blood interactions and the buccal cell degradation, Aβ peptides should also be present in the saliva, as APP is a widely expressed protein in the peripheral tissues. Although the number of studies on the matter is still considerably limited, recent results have shown that salivary Aβ 42 is increased in AD patients, while Aβ 40 does not change [ 148 , 149 , 150 ]. However, there are no studies regarding the Aβ 42 /Aβ 40 ratio in the saliva, which should also be validated considering its significant relevance in the CSF [ 151 ].…”
Section: Saliva Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests different pathogens as triggers of a cerebral chronic neuroinflammatory response (66,67); αsynuclein is involved in important aspects of immune activation, specifically with the innate immune response. It may have a regulatory role in the immune response of peripheric and central neurons (68)(69)(70) and could be involved in the canonic activation of inflammatory pathways (inflammation), as well as the chronic immune response and neurotoxicity (neurodegeneration) (71). This occurs due to the overexpression of Toll-like receptors (TLR) and Nuclear Factor (NF-κB), activating, in turn, the cytokine response cascade.…”
Section: The Neuroinflamatory Response and Synucleinopathymentioning
confidence: 99%
“…In the second contribution, Ashton et al [8] review the use of saliva as a peripheral biospecimen. Our group has shown that Aβ was detectable and elevated in the saliva of AD subjects [9].…”
mentioning
confidence: 99%